Implementation of a tool to enhance evidence-informed decision making in public health: identifying barriers and facilitating factors. (25th May 2016) - van der Heide, Iris; van der Noordt, Maaike; Proper, Karin I; Schoemaker, Casper; van den Berg, Matthijs; Hamberg-van Reenen, Heleen H
Abstract : One of the barriers regarding evidence-informed decision making is the gap between the needs of policy makers and the ways researchers present evidence. This pilot study evaluates the barriers and facilitators to the implementation of a tool to enhance transparent and unambiguous communication on scientific evidence by knowledge workers. Therefore, mixed methods (qualitative and quantitative) were applied. The results indicate that to promote successful implementation of such a tool, efforts should be undertaken to provide time and guidance on how to adapt routines and on how to apply the tool to various products.